The Effect of the Two Stay Two Stray Learning Model Based on a Scientific Approach to Student Competence in Biology Learning - Rizka Putri Alti; Moralita Chatri; Irdawati Irdawati; Vauzia Vauzia (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the effect of the two stay two stray learning model based on a scientific approach to the competence of class XI students at SMAN 3 Pariaman. This type of research is a quasi-experimental research with a randomized control-group posttest only design. The research population was all class XI MIPA students at SMAN 3 Pariaman in the 2022/2023 academic year. Sampling used a purposive sampling technique, so that class XI MIPA 1 (experimental class) and class XI MIPA 3 (control class) were selected. Data analysis techniques using normality test, homogeneity test and hypothesis testing. Testing the hypothesis in the domain of knowledge uses the t test while testing the hypothesis in the domain of attitudes and skills using the Mann Whitney test. The results of the study found that the two stay two stray learning model based on a scientific approach had an effect on the competence in the realm of knowledge, attitudes and skills of class XI students at SMAN 3 Pariaman